ANALISIS STRATEGI PROMOSI MUSEUM KOTA MAKASSAR DALAMMENINGKATKAN JUMLAH PENGUNJUNGPADA EVENT SONGLINE - Muh.Arif Padillah Sulo; Rahmah Fitriana (Communication Sciences Study Program, Universitas Islam Makassar, 2025)
This study aims to analyze the most effective promotional strategy for increasing the number of visitors during the Songline event, as well as to examine the impact of the museum’s promotional strategies in boosting visitor attendance at the Makassar City Museum. The research uses a qualitative method with a descriptive approach. Data collection techniques include in-depth interviews with the Makassar City Department of Culture and several visitors at the location, direct observation of the event implementation at the Makassar City Museum, and data analysis. The results show that the most effective promotional strategy for thisevent is the utilization of social media, particularly Instagram. The Makassar City Museum and the Department of Culture actively disseminated information through posts and stories, using a specific hashtag. Although no paid advertising or formal collaboration with influencers was employed, organic promotion by visitors proved capable of creating a significant viral effect. In addition, support from related institutions such as the Department of Tourism helped distribute information to students and educational institutions, which represented one of the largest visitor groups. This event successfully attracted up to 70,000 visitors during the exhibition period, marking a dramatic increase compared to visitor numbers in previous months. This indicates that social media–based promotional strategies and inter-institutional collaboration have a positive impact on enhancing the museum’s appeal.